Shocks, income diversification and welfare in developing and transition countries - Toman Omar Mahmoud (Christian-Albrechts-Universität zu Kiel, 2010)
This dissertation takes a welfare perspective to analyze how rural households in developing countries manage risks ex-ante and cope with shocks ex-post. The first part looks at risk-coping strategies and analyzes the socio-economic consequences of AIDS-related mortality in rural sub-Saharan Africa. Chapter 2 shows that households in rural Zambia are able to stabilize their per-capita incomes after the death of a prime-age member. Yet, risk-sharing arrangements appear to spread the burden beyond directly afflicted households. Chapter 3 demonstrates for North-Western Tanzania that the age at parental bereavement has important consequences for children's long-term capital accumulation in terms of both health and education. These effects, however, depend on the gender of the deceased parent. Preferences of the surviving parent partly protect same-sex children from the detrimental effects of orphanhood, suggesting that risks are not equally shared within households. The second part of the dissertation explores risk-management strategies and investigates the income diversification patterns of farm households in sub-Saharan Africa. Chapter 4 analyzes the dichotomy of the non-agricultural sector in Western Kenya and the resulting poverty and inequality implications. The results show that only rich households are able to overcome the entry barriers into high-return activities. Low-return activities, however, are not concentrated among the poor. The chapter also provides evidence that high-return non-agricultural activities are associated with increased agricultural productivity. Chapter 5 examines the determinants of diversification in Burkina Faso between 1994 and 2003. Diversification into non-agricultural activities appears to be mainly motivated by insurance motives. Yet, the patterns of diversification also reflect structural change offering better opportunities in the non-farm sector. The final part of the dissertation concentrates on Eastern Europe and looks at the welfare implications of international migration for those who stay behind and the migrants themselves. Chapter 6 examines the reasons for reduced labor supply of migrant-sending households in Moldova. The findings do not support the common view that decreased labor market activity is the result of remittances-driven leisure consumption. Instead, the departure of a migrant appears to raise remaining members' productivity in home production. In addition, young adults in migrant families are substantially more likely to pursue higher education. Chapter 7 investigates the economic drivers of human trafficking. Based on a household survey on human trafficking from Belarus, Bulgaria, Moldova, Romania and Ukraine, the analysis finds that the individual risk of falling victim to human trafficking is closely related to the size of regional migration flows. The reasons are lower recruitment costs for traffickers and, to a lesser extent, negative self-selection into migration. Together, these findings illustrate that rural households in the developing world have developed various informal strategies to cope with shocks and reduce their exposure to risks. While these strategies help households to temporarily smooth income or consumption, they are likely to perpetuate poverty and reduce economic growth in the longer run. Consequently, measures that protect households from risks should play a prominent role in rural development strategies.
urn:nbn:de:gbv:8-diss-55687
Keywords: 330; risks; prime-age mortality; household income; human capital; agricultural activities; non-agricultural activities; international migration; estimation of treatment effects; sub-Saharan Africa; Eastern Europe; AIDS; Sterblichkeit; Haushaltseinkommen; Ländlicher Raum; Spillover-Effekt; Sambia; Kinder; Gesundheit; Alleinerziehende; Bildungsinvestition; Schätzung; Tansania; Landwirtschaft; Produktivität; Ländliches Einkommen; Agrareinkommen; Einkommensverteilung; Ländliche Wirtschaft; Kenia (West); Ländliches Einkommen; Agrareinkommen; Strukturwandel; Burkina Faso; Rücküberweisung (Migranten); Migranten; Familienökonomik; Arbeitsangebot; Moldawien; Menschenhandel; Illegale Einwanderung; Soziales Netzwerk; Familiensoziologie; Unvollkommene Information; Weißrussland; Bulgarien; Moldawien; Rumänien